Development of the Cerebrospinal Fluid in Early Stage after Hemorrhage in the Central Nervous System - Kelbich, Petr; Hejčl, Aleš; Krejsek, Jan; Radovnický, Tomáš; Matuchová, Inka; Lodin, Jan; Špička, Jan; Sameš, Martin; Procházka, Jan; Hanuljaková, Eva; Vachata, Petr (Life (Basel, Switzerland), 2021)
Extravasation of blood in the central nervous system (CNS) represents a very strong damaged associated molecular patterns (DAMP) which is followed by rapid inflammation and can participate in worse outcome of patients. We analyzed cerebrospinal fluid (CSF) from 139 patients after the CNS hemorrhage. We compared 109 survivors (Glasgow Outcome Score (GOS) 5-3) and 30 patients with poor outcomes (GOS 2-1). Statistical evaluations were performed using the Wilcoxon signed-rank test and the Mann-Whitney U test. Almost the same numbers of erythrocytes in both subgroups appeared in days 0-3 (p = 0.927) and a significant increase in patients with GOS 2-1 in days 7-10 after the hemorrhage (p = 0.004) revealed persistence of extravascular blood in the CNS as an adverse factor. We assess 43.3% of patients with GOS 2-1 and only 27.5% of patients with GOS 5-3 with low values of the coefficient of energy balance (KEB < 15.0) in days 0-3 after the hemorrhage as a trend to immediate intensive inflammation in the CNS of patients with poor outcomes. We consider significantly higher concentration of total protein of patients with GOS 2-1 in days 0-3 after hemorrhage (p = 0.008) as the evidence of immediate simultaneously manifested intensive inflammation, swelling of the brain and elevation of intracranial pressure.
Keywords: coefficient of energy balance; inflammation in CNS; cerebrospinal fluid; erythrocytes in CSF; total protein in CSF; neutrophils in CSF; aspartate aminotransferase in CSF; CNS haemorrhage